Galactic synchrotron distribution derived from 152 H ii region absorption features in the full GLEAM survey. Issue 3 (29th June 2018) - Su, H; Macquart, J P; Hurley-Walker, N; McClure-Griffiths, N M; Jackson, C A; Tingay, S J; Tian, W W; Gaensler, B M; McKinley, B; Kapińska, A D; Hindson, L; Hancock, P; et al.
ABSTRACT: We derive the synchrotron distribution in the Milky Way disc from H ii region absorption observations over −40° < l < 40° at six frequencies of 76.2, 83.8, 91.5, 99.2, 106.9, and 114.6 MHz with the GaLactic and Extragalactic All-sky Murchison widefield array survey (GLEAM). We develop a new method of emissivity calculation by taking advantage of the Haslam et al. (1981 ) map and known spectral indices, which enable us to simultaneously derive the emissivity and the optical depth of H ii regions at each frequency. We show our derived synchrotron emissivities based on 152 absorption features of H ii regions using both the method previously adopted in the literature and our improved method. We derive the synchrotron emissivity from H ii regions to the Galactic edge along the line of sight and, for the first time, derive the emissivity from H ii regions to the Sun. These results provide direct information on the distribution of the Galactic magnetic field and cosmic ray electrons for future modelling.